Identification and characterization of a cathepsin K homologue that interacts with pathogen bacteria in black rockfish, Sebastes schlegelii. Issue 98 (March 2020) - He, Shu-wen; Du, Xue; Wang, Guang-hua; Wang, Jing-jing; Xie, Bing; Gu, Qin-qin; Zhang, Min; Gu, Han-jie
Abstract: Cathepsin K belongs to the family of cysteine cathepsins. It is well known that the cysteine cathepsins participate in various physiological processes and host immune defense in mammals. However, in teleost fish, the function of cathepsin K is very limited. In the present study, a cathepsin K homologue (SsCTSK) from the teleost black rockfish ( Sebastes schlegelii ) was identified and examined at expression and functional levels. In silico analysis showed that three domains, including signal peptide, cathepsin propeptide inhibitor I29 domain, and functional domain Pept_C1, are existed in SsCTSK. SsCTSK also possesses a peptidase domain with three catalytically essential residues (Cys25, His162 and Asn183). Phylogenetic profiling indicated that SsCTSK was evolutionally close to the cathepsin K of other teleost fish. Expression of SsCTSK occurred in multiple tissues and was induced by bacterial infection. Purified recombinant SsCTSK (rSsCTSK) exhibited apparent maximal peptidase activity at 45 °C, and its enzymatic activity was remarkably declined in the presence of the cathepsin inhibitor E−64. Moreover, rSsCTSK possesses the ability to bind with PAMPs and bacteria. Finally, knockdown of SsCTSK expression facilitated bacterial invasion in black rockfish. Collectively, these results indicated that SsCTSK functions as a cysteine protease and may serves as a target for pathogen manipulation of host defense system. Highlights: Expression of SsCTSK was upregulated during Vibrio anguillarum infection. rSsCTSK exhibited apparent peptidase activity. rSsCTSK displayed apparent binding activities against LPS, PGN and different bacteria. The knockdown of SsCTSK facilitated bacterial invasion in black rockfish.